Kinetics reactions of Ammonium Nitrate-Sodium Nitrite Reaction and Ammonium Nitrate Emulsion Explosives - Melane, Pumeza (Department of Chemistry, 2014)
The aim of this study was to understand and control the gasification rates in ammonium nitrate emulsion explosive using ammonium nitrate-sodium nitrite reaction. This reaction produces N2 gas which is the sensitizer in emulsion explosives. The NH4NO3-NaNO2 gassing reaction produces N2 gas and so the reaction could be followed by the pressure increase in a closed reaction vessel. The reaction is pH sensitive, so the role of pH was investigated in the pH range 2 to 5. Gasification reactions for unbuffered NH4NO3-NaNO2 reaction were found to be rapid below pH = 3 and maximum pressure was attained within 2 hours of starting the reaction. At pH = 4.5 and 5 the reaction failed to attain maximum pressure. Initial rate of reaction showed sensitivity to pH, the rate of reaction decreasing with increasing pH. The reaction was found to be second order with respect to nitrite species. The effects of three different buffers (potassium hydrogen phthalate, sodium formate and sodium citrate) were also investigated. At pH = 3 pressure traces for the buffered reactions had attained maximum pressure while at pH = 3.5 only sodium citrate buffer had reached a pressure stable state. The presence of the buffers resulted in a lower overall pressure change and absolute pH change and higher rate constants and initial rate of reaction than in their absence. iv A Lewis acid (Zinc Nitrate) was added to the buffered and unbuffered NH4NO3-NaNO2 reactions to investigate a patent claim that addition of a Lewis acid would increase the rate of reaction. The presence of zinc nitrate in the buffered reactions resulted in rapid pressure increase; higher initial rate of reactions than the unbuffered with zinc nitrate. Ammonium nitrate solution was emulsified resulting in an ammonium nitrate emulsion explosive and kinetics of gasification was investigated. The gasification reactions were found to be rapid at pH 3.2, slowing significantly with increased pH as indicated by initial rates of reaction and as predicted by the gasification reaction rate law. Maximum pressure increase was attained within three hours at pH 3.2, whereas reactions conducted at pH 4.0 and 4.5 failed to reach maximum pressure even after 24 hours as evidenced by plots of pressure versus time. The effect of buffers in the ammonium nitrate emulsions was also investigated.